Study on the Storage Characteristics of Minimally Processed of Oranges (Citrus grandis L.) Under Modified Packaging - . Saputera; . Sutrisno; Slamet Susanto; I Wayan Budiastra (PERTETA, 2000)
Orange (Citrus grandis L.) is one of horticulture commodity which is consummed because of its delicious taste and plenty vitamins and minerals that is required by the humm body. The respiration rate of the minimally processed of orange at 10, 15 and 27.5 OC were 8.10, 13.24 and 28.212 ml/kg. h, re.jp,pectivily. The respiration rate of whole (unpeeled) orange at the same storage temperature were 10.15, 19.13 and 42.28 ml/kg. h, respectivily.